2018
DOI: 10.1016/j.colsurfb.2018.07.066
|View full text |Cite
|
Sign up to set email alerts
|

A rational and iterative process for targeted nanoparticle design and validation

Abstract: The lack of understanding of fundamental nano-bio interactions, and difficulties in designing particles stable in complex biological environments are major limitations to their translation into biomedical clinical applications. Here we present a multi-parametric approach to fully characterize targeted nanoparticles, and emphasizes the significant effect that each detail in the synthetic process can have on downstream in vitro results. Through an iterative process, particles were designed, synthesized and teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…This demonstrated not only Au surface was efficiently coated with a dense PEG layer, but also the PEG chains presented a brush conformation as reported previously. 52 Then, a slight decrease in the hydrodynamic size was observed after Protein G conjugation, which could be attributed to the reduction of the electrostatic repulsion between the PEG chains in agreement with the zeta potential values (Table 1). Finally, an increase of ∼32 nm in the hydrodynamic size was recorded after antibody conjugation, which demonstrated that the antibody was efficiently conjugated since the typical size of the IgG is approx.…”
Section: Discussionsupporting
confidence: 74%
“…This demonstrated not only Au surface was efficiently coated with a dense PEG layer, but also the PEG chains presented a brush conformation as reported previously. 52 Then, a slight decrease in the hydrodynamic size was observed after Protein G conjugation, which could be attributed to the reduction of the electrostatic repulsion between the PEG chains in agreement with the zeta potential values (Table 1). Finally, an increase of ∼32 nm in the hydrodynamic size was recorded after antibody conjugation, which demonstrated that the antibody was efficiently conjugated since the typical size of the IgG is approx.…”
Section: Discussionsupporting
confidence: 74%
“…Upon functionalization, an expected increase in size of ∼20 nm was observed in PBS for the NPs (Table 1), indicating a PEG coating with a brush configuration as previously reported [11] . Furthermore, hydrodynamic diameters are comparable for all dye labelled and unlabelled (i. e. no dye, ND) PEGylated AuNPs.…”
Section: Figuresupporting
confidence: 80%
“…receptor-mediated endocytosis or pinocytosis or phagocytosis or other) along with their subsequent intracellular fate [ 53 ]. As such, the initial nanoparticle synthesis itself ultimately dictates the downstream in vivo outcomes, as shown in a recent study by Rodriguez-Lorenzo et al [ 54 ].…”
Section: Discussionmentioning
confidence: 99%